THE QUOTATION IN TIBERIU OLAH’S “SINFONIA GIOCOSA (!?)” - LUPU, Olguţa (Studia Universitatis Babes-Bolyai Musica, 2016)
The study starts with a brief debate on the nature of a text as interference space of preexisting texts or, on the contrary, as an original and autonomic reality. Different aspects of music quotation are then considered: cognoscibility, defamiliarization, incorporation of cultural associations and meanings, visibility, position and integration. The case study (analysis of Tiberiu Olah’s Symphony No.4) reveals an interesting way of incorporating the quotation. The main quotation, deriving from Ode to Joy, is clearly presented only in the end of the Symphony, although its deep structure (the trichord) constitutes the basis of the whole work. Even this late appearance is not a simple quotation; the Beethovenian fragment is transformed, the affirmation turning into a painful and uncertain interrogation. Beside the famous quotation, there are many others, more or less audible, coming from a variety of authors and music spheres (opera, religious music, chamber music, patriotic song, film music). Despite their diversity, the quotations are fastened by a common DNA (the trichord), the work acquiring thus a teleological, centripetal, ordering function.